Segmental myoclonus and basilar artery giant aneurysm case report - J. Pitágoras de Mattos; Ana L. Zuma de Rosso; Eduardo Zayen; Sérgio A. P. Novis (Arquivos de Neuro-Psiquiatria)
A 70 years-old man was admitted at our hospital because of unstable angina pectoris. He had essential hypertension and right hemiplegia from a ischemic stroke two years before admission. On neurologic examination, it was found mental disorientation, unstable emotionality, right spastic hemiparesis with right Babinski sign, and segmental myoclonus affecting the superior lip and the palate (palatal nystagmus) on the right side. On the CT scan, a giant aneurysm of the basilar artery was detected. We conclude that the segmental myoclonus could be explained by ischemic lesions in the Guillain - Mollaret triangle.